Ontogenetic niche partitioning in southern elephant seals from Argentine Patagonia - Campagna, Julieta; Lewis, Mirtha Noemi; González Carman, Victoria; Campagna, Claudio; Guinet, Christophe; Johnson, Mark; Davis, Randall W.; Rodríguez, Diego Hernán; Hindell, Mark A. (Marine Mammal Science)
Elephant seals, Mirounga spp., are highly dimorphic, having different energetic requirements according to age and sex, and foraging in various ecological and oceanographic contexts. Resource partitioning has been shown for the sub-Antarctic populations of southern elephant seals, M. leonina, where colonies are surrounded by narrow shelves that deepen abruptly. In contrast, seals from Península Valdés (Argentina), in the northernmost extent of the breeding range, face an extended, shallow, temperate, and productive continental shelf. We integrated tracking data from 98 animals (juveniles and adults, males and females) gathered over more than two decades, and found that although all available habitats were used, individuals segregated by age and sex. Juvenile males favored shelf habitats, whereas subadult and adult males also used the shelf break. Juvenile females preferred the shelf and the more distant Argentine Basin used by postbreeding and postmolt adult females. Males showed the highest proportion of area-restricted search locations, suggesting more spatially concentrated feeding activity, and likely reflecting a preference for foraging habitat and prey. Our results are consistent with those from other populations, implying that elephant seals show remarkable similarities in habitat use by age and sex classes, despite broad differences in the offshore habitats between sub-Antarctic and temperate ecosystems. Fil: Campagna, Julieta. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Lewis, Mirtha Noemi. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: González Carman, Victoria. Instituto Nacional de Investigaciones y Desarrollo Pesquero; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico ...